SUPPORTING COGNITIVE FUNCTION IN THE ELDERLY WITH BRAIN GYM EXERCISES - Rizka Rohmawati, Nina; Nurcahyaningtyas, Widya; Widi Astutik , Rina; Setyarini, Yanti; Meylinda Prakosa , Mira (Community Service Journal of Indonesia, 2025)
WHO (World Health Organization) classifies the elderly as individuals aged 60 years and over in many developing countries. At this time, humans begin to experience a decline in body organ function because cells experience aging. Although cells become larger and older, they lose the ability to divide and reproduce normally. Not only a decline in physical and cellular function, a decline in cognitive function also occurs in the elderly. Maintaining cognitive function in the elderly (parents) is very important for their well-being. Cognitive activities carried out routinely are thought to be able to maintain excellent cognitive function in the elderly. Community Service with the theme of supporting the cognitive function of the elderly with brain gym exercises has been carried out in Ringinsari Village, Kandat District, Kediri Regency. On August 7, 2024, at 08.00 WIB. Located at the Elderly Posyandu, Ringinsari Village, Kandat District, Kediri Regency. The purpose of this community service activity is to improve cognitive function in the elderly, especially in Ringinsari Village, by practicing Brain Gym. The cognitive function in question is to maintain the balance of brain activity, prevent dementia, and improve memory in the elderly. Brain Gym involves dynamic body movements, which stimulate all parts of the brain to work together. This movement helps optimize blood and oxygen flow to the brain. Brain gym movements can help improve memory function and recall abilities. Brain gym helps improve focus and concentration in the elderly. The implementation of this activity goes through several stages, first submitting a request to the PPK, Bangkesbangpol to the village. In the process of implementing Brain Gym exercises, 41 elderly people attended.